Risk and protective factors associated with health risk behaviours among school learners in Western Cape, South Africa - Godswill N. Osuafor; Chinwe E. Okoli; Reamogetse Phateng (BMC, 2023)
Abstract Background Health risk behaviour is rife among school learners in the Western Cape province. This paper assesses risk and protective factors related to health risk behaviours among high school learners. Method: Longitudinal data were sourced from 2950, 2675 and 2230 at Time 0, Time 1 and Time 2 among grade 8 learners aged 13-18 years between 2012 and 2013. Health risk behaviours were assessed on alcohol consumption, smoking cannabis in the past six months, and ever having sexual intercourse. The sociodemographic variables examined were age, sex, residence, socioeconomic status (SES), family structure and population group. Contextual variables studied were the feeling of learners about the intervention program, participation in religious activities, paid casual work and school sports. Descriptive statistics, bivariate associations and binary logistic analyses predicting health risk behaviours were carried out using generalized linear mixed models after restructuring the data collected at different time points. Result Health risk behaviours increased consistently for alcohol consumption (25.7-42.7%), smoking cannabis (10.4-22.1%) and (22.3-36.0%) engaging in sexual intercourse. Increasing age emerged as a risk factor for all the health risk behaviours: alcohol consumption [OR:1.3 (1.2-1.4), p < 0.001]; smoking cannabis [OR:1.3 (1.2-1.4), p < 0.001] and had sex [OR:1.5 (1.4-1.7), p < 0.001]. Participation in paid casual work also predicted health risk behaviour: alcohol use [OR:1.5 (1.2-1.8), p < 0.001]; smoking cannabis [OR:1.3 (1.0-1.7), p < 0.05] and sex [OR:1.4 (1.1-1.7), p < 0.01]. High SES and feelings about the EPEP programme enhanced alcohol consumption and smoking cannabis. Smoking cannabis was augmented by residing in an urban area. Participation in school sports was associated with increased alcohol consumption and engaging in sexual intercourse. Participation in religious activities was protected against alcohol consumption [OR:0.7 (0.53-0.83), p < 0.001]; and sex [OR: 0.5 (0.4-0.7), p < 0.001]. Being a female and belonging to a coloured population group diminished engaging in sexual intercourse, and the family structure of both parents attenuated involvement in smoking cannabis. Conclusion The findings of the study on risks and protective factors on health risk behaviours mirror those of school-based programmes in developing countries. Learners who participated in paid work and school sports are at risk of adverse health outcomes. Furthermore, participation in religious practices and family structure roles in attenuating health risk behaviours should be integrated and considered in the school-based intervention programme.